Compensatory foraging in Trinidadian guppies: Effects of acute and chronic predation threats. Issue 3 (1st June 2014) - Elvidge, Chris K.; Ramnarine, Indar; Brown, Grant E.
Abstract: In response to acute predation threats, prey may sacrifice foraging opportunities in favour of increased predator avoidance. Under conditions of high or frequent predation risk, such trade-offs may lead to reduced fitness. Here, we test the prediction that prey reduce the costs associated with lost opportunities following acute predation threats by exhibiting short-term compensatory foraging responses. Under semi-natural conditions, we exposed female guppies Poecilia reticulate from high and low predation risk sites to one of three levels of acute predation threat (high, intermediate or low concentrations of conspecific alarm cues). Our results confirm previous reports, demonstrating that guppies from a high predation site were consistently 'bolder' (shorter escape latencies) and exhibited graded threat-sensitive responses to different simulated threat levels while those from the low predation site were 'shyer' and exhibited non-graded responses. Most importantly, we found that when guppies from low predation sites resumed foraging, they did so at rates significantly lower than baseline rates. However, guppies from high predation sites resumed foraging either at rates equal to baseline (in response to low or intermediate risk stimuli) or significantly increased relative to baseline rates (in response to high risk stimuli). Together, these results highlight a complex compensatory behavioral mechanism that may allow prey to reduce the long-term costs associated with predator avoidance.